Rooting of coffee cuttings immersed in tiririca extract - Dias, Jairo Rafael Machado; Silva, Edilaine D’Avila da; Gonçalves, Gerlandio Suassuna; Silva, Jose Ferreira da; Souza, Emanuel Fernando Maia de; Ferreira, Elvino; Stachiw, Rosalvo (Coffee Science - ISSN 1984-3909, 2012)
The cultivation of coffee trees plays an important role in Brazilian agriculture and economy. However, toincrease productivity healthy plants and vigorous seedlings are needed. Vegetative propagation is an excellent optionbecause the new plant maintains the genetic characteristics of the parent plant. To improve rooting the use of exogenoushormones is a technique widely used in this type of propagation. In this case, the hormones used are indole-butyric acid (IBA)and indole acetic acid (IAA). The purple nutsedge, a weed of difficult control, has high levels of IBA and IAA. The aim of thisstudy was to evaluate different concentrations and immersion times of aqueous extract of purple nutsedge roots in coffeeseedlings. The experimental design was completely randomized with four replicates and 10 cuttings per plot in a factorialscheme, which included four concentrations (0, 400, 800 and 1200 g L-1) of purple nutsedge extracts and two exposure times(20 and 120 seconds). After 100 days of the planting the following characteristics were analyzed: volume and number ofroots, plant height, number of leaves, and dry matter yield. The aqueous extract of C. rotundus showed no effect on thenumber and volume of roots. However the other evaluated characteristics were stimulated or inhibited by concentrations ofthe extract. The immersion time of the cuttings can induce roots growth of the cuttings, but 120 seconds of immersion showedsymptoms of toxicity.